TEKNOLOGI FINANSIAL: ANALISIS CUSTOMER EXPERIENCE PADA GO-PAY - Candy; Tony Chandra; Winny Lim; Dastin (Fakultas Ekonomi Universitas IBA, 2022)
Financial technology offers various types of benefits to its customers. This makes the development of the financial technology industry dependent on how the industry can always provide a good and effective customer experience. Studies that discuss customer experience financial technology are still very few. Therefore, this study aims to test whether there is an effect of customer experience on customer loyalty intentions in using financial technology. This study uses the PLS-SEM method to test several hypotheses. The results show that customer experience is positively influenced by perceived value, customer service, service speed and perceived innovation. Then there is also a significant positive effect of customer experience on loyalty intentions. Meanwhile, ease of use and self-confidence have no significant effect.